Effect of Diet and Physical Activity on Cancer Prevention and Control - Demark-Wahnefried, Wendy; Dieli-Conwright, Christina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Diet, physical activity, and body weight status (including body composition) are increasingly recognized as key factors that influence cancer across its continuum. Observational studies as well as basic research in cell culture and animal models provide evidence that several mononutrients and phytochemicals play a protective role either in hindering normal cells from transforming to precancerous lesions or in slowing the dysregulated cell growth that occurs in the later stages of disease. Similar evidence exists for physical activity and body habitus. As findings from these studies emerge, interventions are designed to ultimately test the impact of various dietary and exercise regimens directly on populations at risk - whether that be in individuals who are cancer-free but who may have increased risk due to family history, or in cancer survivors who are at risk for cancer progression or the occurrence of a new second malignancy. This book includes manuscripts that focus on diet, physical activity, and/or weight status in relation to cancer prevention and control, as well as symptom management. The order of articles follows the cancer continuum. The book begins with the role of diet and exercise in the primary prevention of cancer in both normal and high-risk individuals, and then focuses on preventing neoplastic progression in those who are newly diagnosed with the disease. Later chapters center on dietary and physical activity as key factors in cancer survivorship, and finally concluding with works attributing dietary and physical activity factors on cancer survival.